(untitled) (Journal of Academic Finance, 2024)
Purpose: The general objective of the study is to investigate the impact of COVID-19 on digital financial inclusion in Nigeria. However, the study specifically examines the extent to which COVID-19 enhance digital financial services in Imo State Nigeria; the extent to which COVID-19 increase online financial transaction in Imo State Nigeria and the extent to which COVID-19 increase digital financial transaction in the rural areas of Imo State Nigeria. Methodology: The study adopted a quantitative research methodology. Results: Findings revealed that COVID-19 enhanced digital financial service and on-line financial transaction in Imo State Nigeria, but COVID-19 did not significantly increase digital financial transaction in the rural areas of the State. Originality: This is an original manuscript, which deals with the impact of the COVID 19 crisis in a particular geopolitical region of Nigeria in Africa.